Autosomal recessive distal myopathy. - Isaacs, H (1988)
Five patients with an autosomally recessively transmitted distal myopathy were investigated. Of these, three belonged to a single sibship. Studies included electromyography, histological examination of muscle tissue, histochemical, electron microscopical, and biochemical analyses. One of the cases resembled the Nonaka form while the others were regarded as expressions of the commoner variety of recessive distal dystrophy.